"The Un/Deniable Threat to LGBTQ People". Issue 4 (2nd October 2017) - Duarte, Eugenio
Abstract: During the early days of the campaign and Trump administration, popular opinion suggested that the threat to LGBTQ civil rights achievements posed by a Trump administration would be minimal, given Trump's lack of explicit anti-LGBTQ animus. This optimism has been tested. In this article, I argue that, in fact, the potential destructive effect on LGBTQ rights is real but that detecting it requires an appreciation for unconscious projection and distortion. Donald Trump may at times espouse LGBTQ rights with his words, but through his deeds and associations with social conservative groups—who contain and act out his disavowed anti-LGBTQ hostility—he communicates an unconscious message of rejection and hate. Such mystification mirrors what LGBTQ individuals have often encountered in their upbringings and poses insidious threats to our basic security and self-worth. Psychoanalysts are well-positioned for decoding such mixed messages, and it behooves us as a field to bring our skills to bear on the effects of these messages, particularly on LGBTQ youth.